Visualization and Analysis of Research Areas and Hot Topics in the Field of Digital Twins - Lu Gao; Shugang Li; Huimin Guo (IEEE Access, 2024)
In order to comprehensively understand the research situation of digital twin technology, a knowledge map of the digital twin research field is drawn based on 4102 documents in the WoS core collection, using the analysis method of combining scientometrics and knowledge mapping. The results of the study show that digital twin research has gone through three phases: “slow start - rapid rise - significant growth”; in terms of collaborative networks, Centre National de la Recherche Scientifique is the organization with a high number of publications in the world; combined with the hot words and keywords cluster analysis, digital twin research mainly includes hot words such as digital twin, system, framework, simulation, big data, etc. By extracting the keywords with high emergence intensity and reordering them according to the year of emergence, we get the evolution of the emergent words over time and form the formation with fault detection, logistics, process simulation, data analysis and finite element as the main emergent keywords have become the object of high attention of researchers in recent years and become the current research hotspots. On this basis, the visualized knowledge graph is used to mine the frontier hotspots and development trends in the research field, with a view to providing scientific references for the research in the field of digital twins in the world.